MR and CT evaluation of profound neonatal and infantile asphyxia. - Barkovich, A J (American Journal of Neuroradiology, 1992)
PURPOSE To determine the CT and MR characteristics of the brains of infants who have suffered profound asphyxia and correlate those characteristics with pathophysiologic processes.METHODS MR and CT scans of 16 patients who suffered profound hypoxic-ischemic injury in the perinatal (12 patients) and postnatal (4 patients) periods were retrospectively reviewed in a search for characteristic imaging features.RESULTS Injury in the perinatal period: subacute MR showed short T1 and T2 in the ventral lateral thalami, posterolateral lentiform nuclei, posterior mesencephali, and hippocampi; MR 1 to 16 years after injury showed atrophy or T2 prolongation in the aforementioned regions, the lateral geniculate nuclei and perirolandic cerebral cortex. Asphyxia later in infancy: subacute MR showed T2 prolongation in the corpus striatum and most of the cerebral cortex (perirolandic sparing); MR weeks to months later showed atrophy of the aforementioned areas, the lateral geniculate nuclei and hippocampi. Acute CT in both groups showed basal ganglia hypodensity.CONCLUSIONS The injury patterns observed in neonates and infants with profound hypoxic-ischemic injury vary with the age of the patient at the time of the injury. The change in pattern of damage is suggested to be the result of structural and physiologic changes in the maturing brain. The patterns appear to be consistent and are well demonstrated by MR.